2001
DOI: 10.1046/j.1442-2042.2001.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of fosfestrol and diethylstilbestrol in chronic hemodialysis patients with prostate cancer

Abstract: Fosfestrol drip infusion therapy appeared to be safe as an endocrinotherapy for prostate cancer in chronic hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Pharmacokinetic studies have shown that fosfestrol metabolites have a short half-life, supporting its suitability for long-term infusions in the clinic. It relieves the patients' urinary symptoms, such as poor flow, by shrinking the tumor [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies have shown that fosfestrol metabolites have a short half-life, supporting its suitability for long-term infusions in the clinic. It relieves the patients' urinary symptoms, such as poor flow, by shrinking the tumor [2].…”
Section: Introductionmentioning
confidence: 99%